1990
DOI: 10.1080/02786829008959352
|View full text |Cite
|
Sign up to set email alerts
|

Physical Characterization of Cigarette Smoke Aerosol Generated from a Walton Smoke Machine

Abstract: Mainstream cigarette smoke generated using a Walton smoking machine and Kentucky 2R1 research cigarettes was studied. Results ~howed that puff volume and total particulate matter were consistent after the first puff, with average values of 35.6 cm' and 3.37 mg, respectively. The particle size distribution, measured with a multijet cascade impactor, was not related to butt length or relative humidity ( 1 95%), but was strongly dependent on the aging time. Based on simple monodisperse coagulation, the mass media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 19 publications
4
33
0
Order By: Relevance
“…4 and 5. This is in agreement with the experimental results of Chen et al (1990) and Ishizu et al (1980).…”
Section: Comparison Of Theoretical and Experimental Growth Of Cigaretsupporting
confidence: 83%
See 2 more Smart Citations
“…4 and 5. This is in agreement with the experimental results of Chen et al (1990) and Ishizu et al (1980).…”
Section: Comparison Of Theoretical and Experimental Growth Of Cigaretsupporting
confidence: 83%
“…Properties of CSP (M,, p,, F) are available from current literature and are listed in Table 1 for sidestream CSP and Table 2 for mainstream CSP. (Li, 1993) 60 (Li, 1993) 0.98 (Martonen, 1982) 340 (Ishizu et al, 1980) 61 (Ishizu et al, 1980) 1.12 (Chen et al, 1990)…”
Section: Growth Equation For Cigarette Smoke Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerosol dilution is also required to lower aerosol concentrations to within the operational range of some types of measurement instrumentation, e.g., electrical low pressure impactors and fast electric mobility analyzers. However, it has been established that significant amounts of particulate matter can evaporate under typical dilution levels, owing to the presence of volatile components in mainstream smoke (11)(12). The result is that the PSD measured is not reflective of the PSD exiting the cigarette.…”
Section: Introductionmentioning
confidence: 78%
“…A mean average diameter of cigarette mainstream smoke particles in 35 mL puffs of 0.22-0.27 µm was reported, independent from puff number and tip ventilation (up to 84%). The effects of aging time and dilution on particle size distribution were examined by CHEN et al (296). Their results suggested that there was a dilution value critical for the rapid coagulation and evaporation, and the final particle size of the cigarette smoke aerosol -with further dilution having little effect on the decrease of particle size.…”
Section: Mentholmentioning
confidence: 99%